Varietal differences in onion and garlic yield when grown with and without mulch in three years old poplar plantation - Dhiman, R.C.; Gandhi, J.N. (Indian Journal of Agroforestry, 2020)
Results of two experiments conducted simultaneously under three year old poplar plantation and open condition to evaluate the performance of onion and garlic varieties when grown with and without mulch are presented. The experiments were conducted in split-split plot design randomizing plantation and open condition in main plots, mulching treatments in sub-plots and varieties in sub-sub plot treatments with four replications. Onion yield was significantly decreased when grown under poplar plantation but has shown significant increase under mulching treatment when compared with non-mulching treatment. There were significant differences due to varieties in onion. Variety L-28 produced significantly higher yield than variety AFR. Garlic on the other hand, has shown non significant differences when grown under poplar plantation and open conditions, there were, however significant differences in yield due to mulching and varietal treatments. Sprouting of garlic was affected by the mulching sheet. The economic analysis of growing onion and garlic with and without mulch indicates that onion variety L-28 when grown under open conditions with mulching gave maximum profitability of Rs. 19120 per acre whereas, variety G-50 of garlic when grown without mulch under poplar plantation gave Rs. 14483 per acre. Based on the results of these limited experiments, it is concluded that growing of G50 garlic variety could be remunerative under poplar plantations whereas, onion varieties tried under the study are capable of providing comparable returns which are obtained from traditional intercrops when grown with poplar.